Human Chorionic Gonadotropin Regulates the Smad Signaling Pathway by Antagonizing TGF-β in Giant Cell Tumor of Bone - Xu, Tangbing; Xu, Shenglin; Ma, Guangwen; Chang, Jun; Zhang, Chi; Zhou, Ping; Wang, Chao; Xu, Pengfei; Yang, Junjun; Hu, Yong; Wu, Yunfeng (Recent Patents on Anti-Cancer Drug Discovery, 2024)
Background: Giant cell tumor of bone (GCTB) is a locally aggressive bone tumour aggravated by stromal cell proliferation and metastasis.Objective: We investigated the mechanism of action of human chorionic gonadotropin (HCG) in mediating GCTB proliferation and invasion.Methods: The expression of HCG was quantified using quantitative real-time PCR. After the primary stromal cells were isolated and identified, the function of HCG in GCTB was estimated using the cell counting kit-8, flow cytometry, scratch experiment, transwell assay, Western blot, and immunofluorescence. Moreover, the mechanism of HCG was assessed through western blotting.Results: HCG expression was decreased in clinical tissue samples from patients with GCTB. We validated that HCG repressed stromal cell proliferation, migration, invasion, autophagy, and epithelial- mesenchymal transition (EMT) and promoted cell apoptosis in GCTB. We also verified that HCG repressed the autophagy and EMT of stromal cells through the Smad signaling axis in GCTB. HCG inhibited the transduction of the Smad signaling pathway by restraining the binding of the TGF-β II receptor to ligand Activin A.Conclusion: HCG restrained the Smad signaling pathway by antagonizing TGF-β signaling in GCTB. HCG may serve as a useful patent to treat GCTB.
Keywords: Giant cell tumor of bone (GCTB)